Reducing spoon feeding in education / Muniroh Hamat, Siti Balqis Mahlan and Maisurah Shamsuddin - Hamat, Muniroh; Mahlan, Siti Balqis; Shamsuddin, Maisurah (Unit Penerbitan JSKM, 2023)
Spoon-feeding is a common word which literally refers feeding one with a spoon or metaphorically implies denying someone the ability to think or actfor oneself. It can also refer to someone receiving behavioral treatment that both pampers and compromises self-development. Methodologically, this behavioral impediment may impede individual learning and can discourage creativity and innovativeness among the learners in general, and undergraduates. On the other hand, with the introduction of online learning materials gaining center stage in tertiary education, the ever-ready contents at the click of the key serves like manna from heaven for many students at now. Being educators, they believe that independent learning should be proposed via creative teaching and learning, and this also will be examined in the paper through weekly teaching learning activities conducted during the semester. Providing learning materials online or in class may save both facilitators and learners time, cost, and effort. However, such a provision could result to in the restriction of the development of independent thinking and learning Educators' perspectives on spoon-feeding vary according to the research, and this is what this paper aims to investigate. Although providing lecture notes and learning materials to students has been an option, undergraduates can be trained to develop their own learning materials using technology and innovation through innovative and committed teaching by the facilitators themselves.